Key concepts in anti-discriminatory social work - Okitikpi, Toyin; Aymer, Cathy; Sage eBooks (London : SAGE, 2010)
This volume clearly and concisely explains the basic ideas in the field of anti-discriminatory social work.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Social service -- Practice; Discrimination; Social work with minorities; Electronic books